Benefits And Legal Certainty For The Community On Participatory Mapping Services At The Medan City Land Office - Utomo, Wahyu; Kusbianto, Kusbianto; Zuliah, Azmiati (Legalpreneur Journal, 2022)
The purpose of this study was to determine the public service in Medan City Land Office. To find out the administrative system of land mapping in Medan City Land Office. To determine the effectiveness of legal benefits for the community on participatory mapping of Land Services at the Medan City Land Office. The research methods used are normative and empirical juridical research. The nature of the research used in this study is descriptive analysis. Sources of data used in this study are primary and secondary data. The data analysis method used in this study is descriptive qualitative. Based on the results of the study is the National Land Agency (BPN) is a vertical agency, as a vertical unit that organizes Land Services. Vertical service units are service units that are under the ministry / central institution but have services up to the regional level. The National Land Agency (BPN) is a Non-departmental government agency under and responsible to the president and headed by the head of the National Land Agency (BPN).BPN is regulated through Presidential Regulation Number 10 of 2006 concerning the National Land Agency. The administrative system of land registration in the National Land Agency of Medan through the right path that is through the procedures made by the agency to Agrarian. In PP No. 24 of 1997 regulates a number of lands that have been in doubt about the evidence to absenteeism as well as the process and evidence of their rights have been affirmed as land that can be converted into rights according to the Constitution with the development of a legal institution â€œadjudicationâ€ which is regulated in Article 24 FST of PP 24 of 1997. From the provisions of this PP, there are several other things that are the object of conversion or evidence that can be forwarded to be used in the management of land certificates. As for efforts to minimize obstacles undertaken by the Medan Land Office, namely: trying to eradicate scalpers, the need for increased quality and quantity of equipment so that it can be used properly, increased quality human resources means participating in following specifically in the Diploma program or Bachelor's level in cadastral mapping and measurement, seeking costs.